Evaluation of midwifery practices among registered midwives at Witpoort and Lephalale Hospitals in Limpopo Province, South Africa - Maleta, Kgatsere Sarah (My University, 2023)
Background: Midwifery practices have grown in complexity characterized by overload of operational pressure and the need for cost-effective and continuous accessible healthcare services where midwives are expected to adapt swiftly to keep up with the current changes in the settings to provide midwifery care. Midwifery practices are used to maintain quality as an alternative to mandatory legislated standards and can be used for self-assessment or benchmarking. Midwifery care is dynamic and evolving, and as such, failure by midwives to keep up with new developments may be deleterious. Therefore, upskilling clinical programmes such as essential steps to manage obstetric emergencies should be made available to midwives as it may improve clinical expertise. Purpose: The purpose of this study was to evaluate the midwifery practices among registered midwives. Research method: Quantitative, descriptive and cross-sectional research was conducted to assess and describe midwifery practices among registered midwives at Witpoort and Lephalale hospitals in Limpopo province, South Africa. The population was all the registered midwives at Witpoort and Lephalale hospital. The population size was 100 midwives. Sample size of 80 registered midwives determined by Slovin formular. Simple random sampling was used to select the sample. A self-developed questionnaire was piloted before the main study was conducted. Data were analysed using the Statistical Package for Social Sciences (SPSS) version 27 with the assistance of the statistician. Measures to ensure reliability and validity adhered to ensure quality of the study findings. Results: The study revealed that midwifery practices were adversely affected due to lack of the human and material resources; inadequate and malfunctioning equipment and also lack of training. A significant portion (47%) of the registered midwives were aged 50 or older. The majority of the respondents (78%) were female, and 82% did not have a specialty. A large proportion (41%) of the registered midwives had less than 6 years of experience in the maternity unit, while 6% had more than 15 years of experience. The majority (93.3%) of respondents consistently provide emotional support to pregnant women during antenatal care, and 81.6% indicated that they consistently and effectively address the questions and concerns of pregnant women. Most (93.8%) of the respondents monitor the well-being of both the fetus and the mother during high-risk antenatal visits, while 85.7% consistently offer emotional support during labour and childbirth. However, a substantial majority (97.9%) never advised pregnant women to bring doulas for support. The majority (85.7%) of the respondents provide pain relief to pregnant women during labour. About 81.6% of the respondents deliver appropriate care to women during labour and childbirth, but only 34.7% stay with the woman during the second stage of labour. About (81.6%) of the respondents provide health education to mothers during the postpartum period. Approximately 42.8% of the respondents consistently support mothers in initiating and establishing breastfeeding, and 63.3% consistently address complications during the postpartum period. Conclusion: The study concluded that the midwifery practices were sub-standard due to the negative impact posed by lack of resources and equipment, and shortage of midwives, and lack of training. Sub-standard midwifery practices have serious implications for the health and well-being of mothers and newborns. These practices were influenced by various factors such as inadequate material and human resources; lack and malfunctioning of the available equipment. The consequences of inadequate midwifery practices can include increased maternal and neonatal morbidity and mortality rates, complications during childbirth, and long-term health issues for both mothers and infants. Addressing shortage of human and material resources in maternity units is important for ensuring the safety and well-being of pregnant women and their newborns.
Thesis (M. (Nursing)) -- University of Limpopo, 2023
Keywords: Evaluation; Midwifery; Practices; Registered Midwives; Nursing audit; Midwifery -- Standards -- South Africa -- Limpopo; Midwifery -- South Africa -- Limpopo -- Rating off